Age of onset of cannabis use and decision making under uncertainty - Jose Ramón Alameda-Bailén; Pilar Salguero-Alcañiz; Ana Merchán-Clavellino; Susana Paíno-Quesada (PeerJ, 2018)
Objective Cannabis, like other substances, negatively affects health, inducing respiratory problems and mental and cognitive alterations. Memory and learning disorders, as well as executive dysfunctions, are also neuropsychological disorders associated to cannabis use. Recent evidence reveals that cannabis use during adolescence may disrupt the normal development of the brain. This study is aimed to analyze possible differences between early-onset and late-onset cannabis consumers. Method We used a task based on a card game with four decks and different programs of gains/losses. A total of 72 subjects (19 women; 53 men) participated in the study; they were selected through a purposive sampling and divided into three groups: early-onset consumers, late-onset consumers, and control (non-consumers). The task used was the “Cartas” program (computerized version based on the Iowa Gambling Task (IGT)), with two versions: direct and inverse. The computational model “Prospect Valence Learning” (PVL) was applied in order to describe the decision according to four characteristics: utility, loss aversion, recency, and consistency. Results The results evidence worst performance in the IGT in the early-onset consumers as compared to late-onset consumers and control. Differences between groups were also found in the PVL computational model parameters, since the process of decision making of the early-onset consumers was more influenced by the magnitude of the gains-losses, and more determined by short-term results without loss aversion. Conclusions Early onset cannabis use may involve decision-making problems, and therefore intervention programs are necessary in order to reduce the prevalence and delay the onset of cannabis use among teenagers.